The effect of capital adequacy ratio, loan-to-deposit ratio, non-performing loan, and operational efficiency on the rate of return on assets with allowance for impairment losses as moderating variable in conventional banks listed on the Indonesian stock - Khairi, Fachri Randa; Halim, Edyanus Herman; Rokhmawati, Andewi (International Journal of Economic, Business & Applications, 2024)
This study is quantitative research focusing on the effect of specific financial ratios, namely the capital adequacy ratio, loan-to-deposit ratio, non-performing loan, and operating costs on operating income ratio (BOPO), on the return on asset level with impairment loss reserves as moderating variables. The population in this study were conventional banking companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2021 period. A sample of 26 companies was selected using purposive sampling. The data was processed using moderation regression analysis. The results showed that the capital adequacy ratio significantly positively affects return on assets. The loan-to-deposit ratio does not affect the return on assets. Non-performing loans and operating costs of operating income significantly negatively affect the return on assets. Provision for impairment losses as a moderating variable weakens the effect of the capital adequacy ratio variable and operating cost of operating income on return on asset. Impairment loss reserve does not moderate the impact of loan-to-deposit ratio and non-performing loan variables on return on asset.